Healing in the history of Christianity - Porterfield, Amanda, 1947- (Oxford University Press, 2005)
Amanda Porterfield offers a survey of ideas, rituals, & experiences of healing as Christian history. She chronicles changes in healing beliefs & practices through the centuries & considers recent findings about the biological effects of belief.